2007
DOI: 10.1097/01.hp.0000255659.86606.97
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation and Distribution of Uranium in Rats After a Contamination on Intact or Wounded Skin

Abstract: Uranium uptake can occur accidentally by inhalation, ingestion, injection, or absorption through intact or wounded skin. Intact or wounded skin routes of absorption of uranium have received little attention. The aims of our work were (1) to evaluate the influence of the type of wound contamination on the short term distribution and excretion of uranium in rats and (2) to generate data to assess the time available to treat contamination of intact or wounded skin before significant uptake of uranium occurs. Biok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
1
19
0
Order By: Relevance
“…156 (2006) for information on the behavior of uranium and other radionuclides in wounds and a description of a model depicting idealized rates of mobilization of activity to blood. Experimental data on the rate of penetration of uranium through burned, scraped, or intact skin and references to related studies can be found in papers by de Rey et al 1983, Lopez et al 2000, and Petitot et al 2007.…”
Section: Action Levels For Urinary Uranium For Intake Through a Woundmentioning
confidence: 99%
“…156 (2006) for information on the behavior of uranium and other radionuclides in wounds and a description of a model depicting idealized rates of mobilization of activity to blood. Experimental data on the rate of penetration of uranium through burned, scraped, or intact skin and references to related studies can be found in papers by de Rey et al 1983, Lopez et al 2000, and Petitot et al 2007.…”
Section: Action Levels For Urinary Uranium For Intake Through a Woundmentioning
confidence: 99%
“…In hairless rats, dermal exposure to uranyl nitrate resulted in 0.4% of the dose being absorbed (Petitot et al, 2007a(Petitot et al, , 2007b; damage to the skin resulted in higher absorption efficiencies.…”
Section: Uranium Biokineticsmentioning
confidence: 99%
“…The most hydrosoluble uranium compounds, such as uranyl nitrate, have proven to be the most toxic, and their toxicity increases with exposure time and exposed area (Lopez et al, 2000). Uranium intake through the skin is increased when the contamination is associated with a superficial skin lesion, such as a moderate chemical burn (Wu and Fan, 1982;Berard et al, 1994;Petitot et al, 2007aPetitot et al, , 2007b.…”
Section: R E S E a R C H A R T I C L Ementioning
confidence: 99%
“…This mainly concerns accidental chemical contact with skin in a domestic or industrial context. Recent years have witnessed a growing concern for this type of dermal exposure in the industry (Nielsen and Andersen, 2001), particularly in the nuclear industry (Wu and Fan, 1982;Berard et al, 1994;NCRP, 2007;Petitot et al, 2007aPetitot et al, , 2007b.…”
Section: Introductionmentioning
confidence: 99%